Disorders of speech and language in child with agenesis of the corpus callosum - case study - Chrut, Aneta (Journal of Education, Health and Sport, 2018)
Introduction: The corpus callosum is the largest structure of the nerve fibers of the brain. Its main function is to coordinate the transfer of information between the right and left hemispheres of the brain. Agnesis of the corpus callosum is one of the most common defects in the CNS. ACC can be isolated as a defect (approx. 20%) or extend as a disorder co-morbid abnormalities of other systems and organs (approx. 80%). In patients who have a disorder of the corpus callosum work points to the plurality of delays and disturbances. They are related to physiological disorders, developmental, social and disorders of communication, speech and language. The aim of the study was to description of psychomotor impairment in a child with agnesis of the corpus callosum.Material and method: The object of the study was three-year-old girl diagnosed with agnesis of the corpus callosum. Pregnancy was complicated, in the study of prenatal suspicion of CNS defects, threatening preterm delivery at 32 weeks gestation. In neonatal microcephaly found in ultrasound agnesis of the corpus callosum. EEG is abnormal. Made imaging CNS in sedation indicates holoprosencephalię. The current diagnosis of the child is also hypopituitarism, hypernatremia separable and short stature.Conclusions: Agnesis of the corpus callosum is a congenital defect and now there aren’t known methods of treatment of this deficit. Child who has the disorder need to be taken care of multidisciplinary team: neurologist endocrinologist, genetics, optometrist, pediatrician, psychologist, a physiotherapist, and the speech therapist to compensate for developmental deficits.